Theodor Herzl And The Armenian Question According To Marwan Buheiry’s Work - Hovhannisyan, Nikolay (ՀՀ ԳԱԱ)
In the article is discussed the monograph “Theodor Herzl and The Armenian Question” written by the Lebanese scholar Marwan Buheiry, specializing in modern and contemporary history of the Middle East, Arab peoples and international policy of Zionism. The study is devoted to the Armenian-Jewish relations in the early stages of political Zionism.
Keywords: Armenian question; Armenian genocide